Biotic and paleoceanographic changes across the Late Cretaceous Oceanic Anoxic Event 2 in the southern high latitudes (IODP Sites U1513 and U1516, SE Indian Ocean) - Maria Rose Petrizzo; Giulia Amaglio; David K. Watkins; Kenneth G. MacLeod; Brian T. Huber; Takashi Hasegawa; Erik Wolfgring (Paleoceanography and Paleoclimatology, 2022)
Oceanic Anoxic Event 2, spanning the Cenomanian/Turonian boundary (93.9 Ma), was an episode of major perturbations in the global carbon cycle. To investigate the response of biota and the paleoceanographic conditions across this event, we present data from International Ocean Discovery Program sites U1513 and U1516 in the Mentelle Basin (offshore SW Australia; paleolatitude 59 degrees-60 degrees S in the mid-Cretaceous) that register the first complete records of OAE 2 at southern high latitudes. Calcareous nannofossils provide a reliable bio-chronostratigraphic framework. The distribution and abundance patterns of planktonic and benthic foraminifera, radiolaria, and calcispheres permit interpretation of the dynamics of the water mass stratification and provide support for the paleobathymetric reconstruction of the two sites, with Site U1513 located northwest of the Mentelle Basin depocenter and at a deeper depth than Site U1516. The lower OAE 2 interval is characterized by reduced water mass stratification with alternating episodes of enhanced surface water productivity and variations of the thickness of the mixed layer as indicated by the fluctuations in abundance of the intermediate dwelling planktonic foraminifera. The middle OAE 2 interval contains lithologies composed almost entirely of radiolaria reflecting extremely high marine productivity; the low CaCO3 content is consistent with marked shoaling of the Carbonate Compensation Depth and ocean acidification because of CaCO3 undersaturation. Conditions moderated after deposition of the silica-rich, CaCO3-poor rocks as reflected by the microfossil changes indicating a relatively stable water column although episodes of enhanced eutrophy did continue into the lower Turonian at Site U1516.